2019
DOI: 10.1021/acs.nanolett.9b00423
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-Assisted Self-Assembly and Synthesis of Size-Controlled Porphyrin Nanocrystals with Enhanced Photocatalytic Hydrogen Evolution

Abstract: Design and engineering of highly efficient light-harvesting nanomaterial systems to emulate natural photosynthesis for maximizing energy conversion have stimulated extensive efforts. Here we present a new class of photoactive semiconductor nanocrystals that exhibit high-efficiency energy transfer for enhanced photocatalytic hydrogen production under visible light. These nanocrystals are formed through noncovalent self-assembly of In­(III) meso-tetraphenylporphine chloride (InTPP) during microemulsion assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…It was reported that the bottom of the lowest unoccupied molecular orbital (LUMO) in many n‐type semiconductors is approximately equal to the flat band potential . The energy band gap of the assemblies 1 and 2 were determined by Tauc plots with the estimated value of 1.82 and 1.96 eV, respectively, Figure , which are match well those of porphyrin‐based nanorods reported previously . Therefore, the highest occupied molecular orbital (HOMO) can be estimated as 1.47 and 1.60 V versus NHE.…”
Section: Resultssupporting
confidence: 84%
“…It was reported that the bottom of the lowest unoccupied molecular orbital (LUMO) in many n‐type semiconductors is approximately equal to the flat band potential . The energy band gap of the assemblies 1 and 2 were determined by Tauc plots with the estimated value of 1.82 and 1.96 eV, respectively, Figure , which are match well those of porphyrin‐based nanorods reported previously . Therefore, the highest occupied molecular orbital (HOMO) can be estimated as 1.47 and 1.60 V versus NHE.…”
Section: Resultssupporting
confidence: 84%
“…The reported research includes meso‐tetrakis (4‐sulfonatophenyl)‐porphyrin cobalt (CoTPPS) homogeneous hydrogen production, [ 44 ] meso‐tetra(4‐pyridyl) porphine zinc (ZnTPyP) assembly, [ 45 ] and In(III) meso‐tetraphenylporphine chloride (InTPP) nanorods. [ 46 ] More importantly, the essential mechanism about how metal centers regulate supramolecular porphyrin photocatalysts to realize high performance is still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The reported research includes meso-tetrakis (4-sulfonatophenyl)-porphyrin cobalt (CoTPPS) homogeneous hydrogen production, [44] mesotetra(4-pyridyl) porphine zinc (ZnTPyP) assembly, [45] and In(III) meso-tetraphenylporphine chloride (InTPP) nanorods. [46] More importantly, the essential mechanism about how metal centers regulate supramolecular porphyrin photocatalysts to realize high performance is still rarely reported.Here, we focus on fabricating a metalloporphyrin-based supramolecular host photocatalyst through regulating band structure and separation abilities of photogenerated carriers for high efficiency photocatalytic activity. The meso-tetrakis (4-carboxyphenyl) porphyrin (TCPP) is chosen as the basic building block, because the carboxyl group is an extensively studied substituent with a strong electron-withdrawing effect in porphyrin-based photocatalysts and the TCPP self-assembly shows good photocatalytic performance.…”
mentioning
confidence: 99%
“…For some organic aggregates, HOMO and LUMO of π-stacked molecules were overlapped and formed electronic energy level-like structures with conduction bands (CB) and valence bands (VB). Herein, the Mott-Schottky plots of CTAB-TCPP aggregates and EG-TCPP aggregates were used to determine the electronic energy levels and the results are shown in Figures S3 and S4 [37,38]. The flat band potential (Efb) for CTAB-TCPP aggregates and EG-TCPP aggregates were−1.04 eV and −0.76 eV (vs. SCE), respectively.…”
Section: Resultsmentioning
confidence: 99%